PENGARUH KOMUNIKASI KELOMPOK TERHADAP KESADARAN MENGGUNAKAN HIJAB PADA IBU-IBU PERWIRITAN MARINDAL I KELURAHAN HARJOSARI II KECAMATAN MEDAN AMPLAS KOTA MEDAN - Siti Rahmah Putri (SYMBOLE, 2025)
This research aims to determine the influence of the communication group, namely the wiritan, on the awareness of using the hijab among the women of the Marindal 1 wiritan, Harjosari II sub-district. This research is quantitative research. The population is all members of the Al-Qomar marindal 1 command, Harjosari II sub-district, Medan Amplas District, Medan City. The sample for this research was all members of the Al-Qomar military service, namely 60 members of the military service. The sampling technique used in this research was total sampling. Data collection techniques used in this research were in two ways, namely interviews and distributing questionnaires. The data analysis technique used is a single analysis table, and hypothesis testing uses descriptive statistical analysis with SPSS version 26. The correlation coefficient obtained shows the number 0.364, in other words the influence of group communication that is carried out has a positive influence on awareness of wearing the hijab among women who wear the hijab. marindal 1, Harjosari II sub-district, Medan Amplas District, Medan City